Corporate governance : the of international business in journal society : governance and CSR management in sport - Breitbarth, Tim (Corporate governance ;, 2015)
The idea for this e-book largely emerged during the 2013 and 2014 EASM conference workshops held in Istanbul (Turkey) and Coventry (UK), respectively. These two scholarly gatherings, which attracted more than 25 research-based presentations, coupled with panel discussions with senior CSR executives from various types of sport organisations to foster theory-practice interaction, signalled the need for a well-rounded understanding of the management and governance of CSR in sport. During these workshops, the idiosyncratic nature of the sport sector was evident. For example, topics included: cultu.